MARKETING INNOVATION THROUGH SOCIAL MEDIA: A CASE STUDY OF A TECHNOLOGY COMPANY - Ignatius Septo Pramesworo; Suslinawati; Ari Jumadi Kirnadi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This article discusses the impact of marketing innovation through social media on the performance of technology companies. Social media marketing innovation includes the creative use of various platform features, data-driven strategies, and active interaction with customers. Through the literature results obtained, this study found that social media plays an important role in increasing brand visibility, strengthening relationships with customers, and optimising marketing decisions. The analysis showed that companies adopting this strategy experienced significant improvements in brand awareness, customer satisfaction, and operational efficiency. Thus, marketing innovation through social media drives the growth and success of technology companies in an increasingly competitive business environment.